Perlindungan Konsumen atas Pencabutan Izin Usaha BPR oleh Otoritas Jasa Keuangan - Asri Elies Alamanda; Darminto Hartono (Journal of Judicial Review, 2021)
The revocation of the Rural Bank (BPR) business license is inseparable from the function of the OJK in fostering and supervising the BPR. This study used an empirical legal research method, namely research was conducted at OJK Regional 3 Central Java and Yogyakarta Special Region. The results indicate that there are 2 legal protections provided by the government to depositors of funds, namely preventive and repressive legal protection. Preventive legal protection has the character of preventing problems, including the application of the principles of confidentiality and prudence. Meanwhile, the repressive legal protection that functions to resolve disputes that arise is the Deposit Insurance Corporation (LPS). Then the factors that cause the revocation of the BPR's business license are factors that come from internal BPRs that cannot manage the BPR properly. The revocation of the RB's business license was caused by 2 things, namely the revocation of the business license at the request of the shareholders and the revocation of the business license because the rescue efforts carried out did not bear fruit.